Solving Schrodinger Equations Using Kashuri and Fundo Transform Decomposition Method - J. Kadhum, Huda; H. Al-Fayadh, Ali (Al-Nahrain Journal of Science, 2022)
This paper proposes a hybrid method that combines the Kashuri and Fundo integral transform and the Adomian decomposition method to solve two types of Schrödinger equations. The exact solutions are successfully found, and the results are compared with those obtained by the existing methods. The obtained results show the accuracy and efficiency of the method.